2013
DOI: 10.1111/tbj.12149
|View full text |Cite
|
Sign up to set email alerts
|

Neo‐adjuvant Capecitabine Chemotherapy in Women with Newly Diagnosed Locally Advanced Breast Cancer in a Resource‐poor Setting (Nigeria): Efficacy and Safety in a Phase II Feasibility Study

Abstract: The majority of clinical trials of neo-adjuvant therapy for breast cancer have been conducted in resource-rich countries. We chose Nigeria, a resource-poor country, as the major site for a phase II feasibility open-label multicenter clinical trial designed to evaluate the efficacy, safety, and tolerability of neo-adjuvant capecitabine in locally advanced breast cancer (LABC). Planned treatment consisted of 24 weeks of capecitabine at a dose of 1,000 mg/m2 twice daily (2,000 mg/m2 total per day). The primary en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…This conforms with findings documented elsewhere in Nigeria where tumors are large (10,17), but contrary to chiedozi's findings where the chemotherapeutic dosing and scheduling were optimal (8,17).…”
Section: Discussionsupporting
confidence: 90%
“…This conforms with findings documented elsewhere in Nigeria where tumors are large (10,17), but contrary to chiedozi's findings where the chemotherapeutic dosing and scheduling were optimal (8,17).…”
Section: Discussionsupporting
confidence: 90%
“…A phase II trial from Nigeria that included 16 patients who received primary systemic capecitabine for over 24 weeks found that the overall response was 44% after 8 cycles [37]. A study from Egypt reported on gemcitabine and cisplatin in locally advanced or metastatic BC after previous anthracycline therapy.…”
Section: Surgery and Adjuvant Treatment Of Bcmentioning
confidence: 99%
“…Capecitabine has also been used was neoadjuvant chemotherapy for breast cancer. Arowolo et al reported that capecitabine monotherapy achieved good overall response rates with manageable toxicity when administered as neoadjuvant chemotherapy to 16 patients with locally advanced breast cancer (16). In a phase II study by Tolaney et al, 3 patients exhibited a complete clinical response after 4 cycles of capecitabine monotherapy and 8 patients exhibited a partial clinical response among 24 women with operable hormone receptor-positive breast cancer (17).…”
Section: Discussionmentioning
confidence: 99%